Vestibular neuronitis - V. A. Parfenov (Медицинский совет, 2021)
Vestibular neuronitis occurs as a result of damage to the vestibular nerve and is manifested by a sudden and prolonged attack of vestibular vertigo, accompanied by nausea, vomiting and imbalance. Questions of etiology, pathogenesis, clinical picture, diagnosis and treatment of VN are discussed. The disease is associated with selective inflammation (viral or infectious-allergic genesis) of the vestibular nerve. The role of herpes simplex virus type 1 is confirmed by cases of herpetic encephalitis in VN. In 2020, cases of VN development in patients with COVID-19 are described. VN usually affects the upper branch of the vestibular nerve, which innervates the horizontal and anterior semicircular canals. The duration of vertigo with VN ranges from several hours to several days. The timing of the restoration of vestibular function depends on the degree of damage to the vestibular nerve, the speed of central vestibular compensation and the patient’s performance of vestibular gymnastics. Some patients, months and even years after VN, experience significant instability. The diagnosis of VL is based on the clinical picture of the disease, the results of an otoneurological examination, and the exclusion of other diseases. VN treatment is aimed at reducing dizziness, nausea and vomiting and accelerating vestibular compensation. In our country VN is rarely diagnosed, which is associated with poor awareness of doctors about this disease. The article presents the observation of a 46-year-old patient with VN, who was mistakenly diagnosed with vertebrobasilar insufficiency, which contributed to the patient’s long-term disability. Establishing the correct diagnosis, educational work with the patient, conducting vestibular gymnastics led to an improvement in the condition, regression of instability. The issues of the effectiveness of vestibular gymnastics, the use of betahistine to accelerate the recovery of patients with VN are discussed.